Queer Mineralogy and the Depths of Hell: Sulfuric Skills, Early Modern England, and the North American Frontier - Kettler, Andrew (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2019)
Levels of environmental apprehension are determined by how threatening embodied sensations deem ecological hazards. This may seem a simple categorization regarding human choice to participate in environmental activism. However, as energy conglomerates work to hide their malfeasance, modern selves rarely experience environmental decline through the five senses. The distances between the modern self and ecological hazards, both physical and discursive, emerge because the superstructure develops defense mechanisms that protect polluters. Encountering sulfur in the English environment, prior to the Industrial Revolution, consistently meant that evil was moving within the preternatural realm. The external sensing of evil through the sensory signatures of sulfur was a form of sense work within the phenomenological space between the supernatural and the natural. Throughout the Early Modern Era, the idea that sensing sulfur signified evil or malevolence faded. Because coal and her sulfuric sensory traits became vital to the establishment of the Industrial Revolution, embodied changes were forced to occur, essentially through the creation of a false sensory consciousness that defined sulfuric sensations as positive markers of progress, profit, and purity. Upon the frontiers of the commonwealth and the newly established United States, these sensations persisted. The early frontiers of North America offer historical spaces where individuals marched westward and educated their senses to discover profit. Sulfuric connotations of evil were rarely considered, as frontiersmen educated their senses beneath a superstructure that defined associations with sulfur as preternaturally safe. Sensory skills were negotiated and educated to catch coal and sulfur through greater and more refined tactile, nasal, flavorful, visual, and aural skills. These sensory pedagogies inhabited somatic work farther west into British Columbia, known for explosive environmental conditions due to large coal supplies, indigenous populations, sacred alimentary goods, and amazing natural beauty. How citizens decide to become activated to environmental concern, as within modern Vancouver and her sulfur mounds, arises through whether the socially constructed senses ever perceive pollution as corruptive.